Rodent incisor as a model to study mesenchymal stem cells in tissue homeostasis and repair - Jing, Junjun; Zhang, Mingyi; Guo, Tingwei; Pei, Fei; Yang, Yuchen; Chai, Yang (Frontiers in Dental Medicine, 2022)
The homeostasis of adult tissues, such as skin, hair, blood, and bone, requires continuous generation of differentiated progeny of stem cells. The rodent incisor undergoes constant renewal and can provide an extraordinary model for studying stem cells and their progeny in adult tissue homeostasis, cell differentiation and injury-induced regeneration. Meanwhile, cellular heterogeneity in the mouse incisor also provides an opportunity to study cell-cell communication between different cell types, including interactions between stem cells and their niche environment. More importantly, the molecular and cellular regulatory mechanisms revealed by the mouse incisor have broad implications for other organs. Here we review recent findings and advances using the mouse incisor as a model, including perspectives on the heterogeneity of cells in the mesenchyme, the niche environment, and signaling networks that regulate stem cell behavior. The progress from this field will not only expand the knowledge of stem cells and organogenesis, but also bridge a gap between animal models and tissue regeneration.